Implementation of Erp-based Automated Inventory Management System at Sabana Fried Chicken Franchise Company - Cahyono, Antonius; Manik Ayu Titisari; M. Nusron Ali M (Cv. Syntax Corporation Indonesia, 2023)
The implementation of an Automated Inventory Management System (AIMS) based on Enterprise Resource Planning (ERP) has a crucial role in improving the operational efficiency of franchise companies. This study investigates the AIMS implementation strategy for Sabana Fried Chicken, detailing the process and benefits. Qualitative approaches and literature analysis are used to deeply understand this implementation. Sabana Fried Chicken adopts JD Edwards Enterprise One 9.0 to manage accounting and inventory. The system facilitates tight control over inventory, allowing store managers to accurately plan, manage, and forecast inventory. In addition, this system also simplifies the process of journal entry, allocation, and bank account reconciliation. A deep understanding of the Operational Information System, Enterprise Collaboration System, Sabana Fried Chicken Management System, and Sabana Fried Chicken's Field Management System was revealed. Successful implementation is supported by comprehensive employee training, efficient inventory management, as well as adaptation to fluctuations in customer demand. Risk coverage analysis and SWOT analysis highlight the challenges and opportunities facing companies, with strategic recommendations to address risks and capitalize on existing opportunities. This research provides in-depth insight into AIMS implementation strategies in franchise companies and makes important contributions to the inventory management and ERP literature. The findings are expected to guide other companies in facing similar challenges and harnessing the full potential of technology to improve their efficiency and competitiveness.